A glycoengineered antigen exploiting a conserved protein O-glycosylation pathway in the Burkholderia genus for detection of glanders infections. Issue 1 (31st December 2021) - Wang, Guanbo; Glaser, Lena; Scott, Nichollas E.; Fathy Mohamed, Yasmine; Ingram, Rebecca; Laroucau, Karine; Valvano, Miguel A.
ABSTRACT: We recently described a protein O -glycosylation pathway conserved in all species of the Burkholderia genus that results in the synthesis and incorporation of a trisaccharide glycan to membrane-exported proteins. Here, we exploited this system to construct and evaluate a diagnostic tool for glanders. Burkholderia mallei, the causative agent of glanders, is a highly infectious and fatal zoonotic pathogen that infects horses, mules, donkeys, and occasionally humans. A highly sensitive and specific diagnostic tool is crucial for the control, elimination, and eradication of B. mallei infections. We constructed plasmids carrying synthetic genes encoding a modified, previously unannotated Burkholderia glycoprotein containing three glycosylation sequons fused to the cholera toxin B-subunit. The resulting proteins were glycosylated in the B. cenocepacia K56-2 parental strain, but not in glycosylation-deficient mutants, as determined by SDS-PAGE and fluorescent lectin blots. One of these glycoproteins was used as an antigen in ELISA and western blots to screen a panel of serum samples collected from glanders-infected and healthy horses, which were previously investigated by complement fixation test and indirect ELISA based on a semi-purified fraction of B. mallei . We show that ELISA and western blot assays based on our glycoprotein antigen provide 100% specificity, with a sensitivity greater than 88%. The glycoprotein antigen was recognized by serum samples collected from patients infected with B. pseudomallei, B. mallei, B. multivorans, and B. cenocepacia . Our results indicate that protein O -glycosylation in Burkholderia can be exploited as a biomarker for diagnosis of Burkholderia -associated infections.